O elegante sport : conexões entre a moda, a modernidade e o ciclismo em Porto Alegre (1895-1905) - Santucci, Natália de Noronha (2016)
This thesis covers the beginning of the cycling practice in Porto Alegre (1895-1905) and the clothes used by its adepts, both under the perspective of fashion. Fashion, understood here like a social phenomenon without specific content, is present in many fields of the social life. Even though personal looks are its clearer expression, fashion also covers behaviors. It seeks to contextualize the called "cycling fashion", which spreaded along the occident at the end of the XIX century, from the big European centers to the small provinces. In this time the development of new types of bikes made it possible for more people to use it - like older men and women. The new practice diffusion demanded appropriate clothing, since it wasn’t possible to ride these bikes using the suitable clothes of the time. Because of this many proposals of new clothes were presented, causing different reactions - the female clothing, for instance, created controversy for being close to a symbolic challenge to the gender roles, strongly set by that time. The cyclists unions encouraged the adoption of uniforms. In Porto Alegre, on the selected 10 years timeframe, there were two important associations - the União Velocipedica de Amadores and the Radfahrer Verein Blitz - from where fashion will be considered on its two aspects - the habits and the clothing. This paper will analyze speeches about the cycling clothes present on Brazilian newspapers in that time and how it was used by the people from Porto Alegre that shared the love for bikes, from evidences provided by the press and photography. In short, it’ll be discussed the connections between fashion, modernity and cycling in Porto Alegre.